Influence of nickel-plating on laser weldability of aluminium busbars for lithium-ion battery interconnects - M Chelladurai Asirvatham; Iain Masters; Geoff West; Christopher Harris (Journal of Materials Research and Technology)
This study investigates the influence of nickel-plating method and thickness on the laser weldability of aluminium busbars for lithium-ion battery cell interconnects. Three nickel plating methods (electroless medium phosphorus, electrolytic bright, and sulfamate) were employed at 3, 9, and 15 μm thicknesses. Laser welding was performed, and the welds were characterised for mechanical strength, microstructural features, and porosity. Results demonstrate that nickel plating significantly influences weldability, with weld strength increasing from 1 kN to 1.5 kN with increasing plating thickness. Bright and electroless nickel plating exhibited superior weld strength and hardness compared to sulfamate plating. The weld hardness ranges from 60 to 75 HV at a plating thickness of 3 μm, increases to 100–120 HV at 9 μm, and rises to 150–200 HV at 15 μm for bright and electroless nickel plating. In contrast, sulfamate plating at 15 μm exhibits a slightly lower hardness of 100–150 HV. The weld fracture surface analysis reveals a transition in failure mode from ductile to mixed ductile/brittle, indicating the presence of increasing hard phases. Similarly thicker plating generally increased porosity, sulfamate plating exhibited low porosity (1.5 %) even at high thicknesses, in contrast to bright (10 %) and electroless (3.1 %). Microstructural analysis revealed the formation of an Al–Ni eutectic structure with hard Al3Ni intermetallics dispersed within a softer α-Al matrix, contributing to the observed improvements in mechanical properties. This study provides valuable insights into optimising nickel-plating parameters for enhanced weldability and improved performance of aluminium busbars in battery cell interconnects.